2014
DOI: 10.1371/journal.pone.0112886
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nidogen-1/Laminin γ1 Interaction by Cross-Linking, Mass Spectrometry, and Computational Modeling Reveals Multiple Binding Modes

Abstract: We describe the detailed structural investigation of nidogen-1/laminin γ1 complexes using full-length nidogen-1 and a number of laminin γ1 variants. The interactions of nidogen-1 with laminin variants γ1 LEb2–4, γ1 LEb2–4 N836D, γ1 short arm, and γ1 short arm N836D were investigated by applying a combination of (photo-)chemical cross-linking, high-resolution mass spectrometry, and computational modeling. In addition, surface plasmon resonance and ELISA studies were used to determine kinetic constants of the ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 69 publications
1
43
0
Order By: Relevance
“…Quite often it has been found that a subset of the highly reliable cross-links cannot be explained by the known structure of the protein or protein complex, or these cross-links are inconsistent with other cross-links or other experimental data (12,13,17,18). In those cases, the over-length cross-links were often discarded or the corresponding distance restraints were relaxed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quite often it has been found that a subset of the highly reliable cross-links cannot be explained by the known structure of the protein or protein complex, or these cross-links are inconsistent with other cross-links or other experimental data (12,13,17,18). In those cases, the over-length cross-links were often discarded or the corresponding distance restraints were relaxed.…”
Section: Discussionmentioning
confidence: 99%
“…CXMS-based structural modeling has been explored using various software tools, yet a lot of these studies aimed for a single structure that had the lowest energy and best satisfied the experimental data (11,13,24,25). To fully account for the intramolecular cross-links, we developed the DynaXL method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, three L4 domains are found in perlecan, a heparan sulfate proteoglycan of the ECM with an origin as ancient as that of laminin. No experimentally determined structure for an L4 domain has been reported, though a fold prediction based on threading has been made . We produced recombinant versions of the human laminin α1 and α2 L4b domains to investigate the L4 structure at high resolution and to provide a framework for exploring the functions and structural diversification of laminin internal domains.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of NMR restraints is considered by their relative contributions in the scoring function. Distance constraints can be enforced (e.g., [47]) as part of the scoring function involving statistical interaction potentials and evaluation of standard geometry (atoms and secondary structures) and clashes. In a recent structure of S. flexneri type III secretion system (T3SS) needle several solid-state NMR (ssNMR) distance restraints were used to build models with a 7.7 Å cryo EM density map [48].…”
Section: Approaches To Integrative Modellingmentioning
confidence: 99%